The Effect Of Murrotal Al-Quran Therapy Onreducing The Intensity Of Labor Pain In The First Stage Active Phase - Maulina Mawaddah; Eka Sylviana Siregar (International Journal of Medicine and Health, 2024)
Childbirth is a natural way that every mother must go through where the results of conception in the form of a baby and placenta are released from the uterus. Normal labor is characterized by uterine contractions that cause thinning, dilation of the cervix and push the fetus out through the birth canal, causing a sensation of pain felt by the mother. The purpose of this study was to determine whether there is an Effect of Murrotal Al-Qur'an Therapy on Reducing the Intensity of Labor Pain in the First Active Phase at the Juliana Dalimunthe Clinic. The research method used was Pre-Experiment One Group Pre and Posttest Design. Samples were taken by Accidental Sampling from mothers in the first active phase of labor who met the inclusion criteria totaling 30 people. Data collection was carried out using a face pain rating scale questionnaire. Data analysis with the Shapiro Wilk test and tested with the Wilcoxon Signed Ranks test statistical test. The results of the study conducted from May to July, found the average pain scale before therapy was 6.83 and the average after therapy was 6.17, the decrease in pain scale from before to after Murottal therapy was 0.66. From the statistical test, the P value = 0.001 was obtained, indicating that there was an effect of Murottal Al-Qur'an therapy on reducing the intensity of labor pain. The conclusion of this study is that the provision of Murottal Al-Qur'an therapy has been proven to be able to reduce labor pain in the first active phase. It is hoped that the provision of Murottal Al-Qur'an therapy will be an alternative intervention in reducing labor pain in the first active phase.